Application Development of Coronary Heart Disease Expert System Using Android-Based Agile Scrumban Method - Untung Suropati; Rasiban; Dadang Iskandar Mulyana (Yayasan Sinergi Multidimensi Kreatif, 2024)
The purpose of the research is to develop an application for coronary heart disease diagnosis expert system using the Android-based Agile Scrumban method. Coronary heart disease is one of the causes of death in the world, so an effective and efficient application is needed in providing information and early diagnosis as well as early symptoms so that it can save many lives. The Agile Scrumban method was chosen because of its flexibility in project management and its ability to handle changes in user needs quickly. The application is developed with requirements analysis, interface design, implementation, and testing. The application developed can make it easier for users to access information related to symptoms, risk factors, and recommendations for actions that need to be taken. The results of the study show that the application has succeeded in providing an accurate initial diagnosis and getting a positive impact response from users. Community diagnostic applications can be more aware of the risk of coronary heart disease and take the necessary preventive steps. This study shows the potential of the application of information technology in the health sector to increase awareness and handle coronary heart disease more efficiently. Android-based applications can make it easier for users of coronary heart disease to make it more efficient because they can be used on android devices.